2020
DOI: 10.1155/2020/4936423
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the NoSAS Score for the Screening of Sleep-Disordered Breathing in a Sleep Clinic

Abstract: Background. There is a growing number of patients with sleep-disordered breathing (SDB) referred to sleep clinics. Therefore, a simple but useful screening tool is urgent. The NoSAS score, containing only five items, has been developed and validated in population-based studies. Aim. To evaluate the performance of the NoSAS score for the screening of SDB patients from a sleep clinic in China, and to compare the predictive value of the NoSAS score with the STOP-Bang questionnaire. Methods. We enrolled consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Although these questionnaires can diagnose sleep disordered breathing, an umbrella term with a prevalence of 24.0%–83.8% ( 48 51 ), OSA is the most frequent type ( 52 ). In addition, No-SAS score has shown high sensitivity and specificity for OSA screening, compared with polysomnography, and has been validated in a Chinese population ( 31 , 53 ). Moreover, it is not feasible to perform PSG in population-based studies due to its cost and technique dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Although these questionnaires can diagnose sleep disordered breathing, an umbrella term with a prevalence of 24.0%–83.8% ( 48 51 ), OSA is the most frequent type ( 52 ). In addition, No-SAS score has shown high sensitivity and specificity for OSA screening, compared with polysomnography, and has been validated in a Chinese population ( 31 , 53 ). Moreover, it is not feasible to perform PSG in population-based studies due to its cost and technique dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend polysomnography (PSG) as the gold standard for SDB assessment, which is an expensive time-consuming, labor-intensive, and technique dependent equipment, and inconvenient to be utilized in large scale population-based studies [ 22 ]. Nonetheless, NOSAS scale is a simple, efficient, and easy method for screening of self-reported SDB [ 23 ] and validated in some of Chinese population [ 24 , 25 ] with a high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported the diagnostic performance of the STOP-Bang questionnaire in different Asian ethnic groups using either the standard BMI (35 kg/m 2 ) or a lower BMI threshold. [9][10][11][12][13][14][15][16][17][18][19][20][21] These studies followed younger patients, most of whom had been referred to sleep clinics. The diagnostic performance of the STOP-Bang questionnaire in the older surgical patients of the different Asian groups remained unknown.…”
Section: Introductionmentioning
confidence: 99%